THE INFLUENCE OF EMPLOYEE ENGAGEMENT, WORKPLACE RECREATION AND WORKPLACE DIVERSITY ON EMPLOYEE PRODUCTIVITY AT PT. WENANG PERMAI SENTOSA MANADO - Kumambong, Novita Regina; Pangemanan, Sifrid S.; AlfaTumbuan, Willem J.F (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2016)
Each company always want to have employees with a highly performance or productivity when work and also have ability to support company for a good performance to achieve the goal. More productivity means more outcomes, more outcomes mean more revenue, and having more revenue guaranteed the sustainability of the business. PT. Wenang Permai Sentosa is a "sister company" or subsidiary of AKR, Tbk, go-public company in Jakarta, that has contributed greatly to the development of business in Indonesia for over 50 years. In this study, population refers to the employees of PT. Wenang Permai Sentosa Manado by using saturation sampling technique and sample size of 102 respondents through questionnaires. This study used multiple regression analysis method. Result shows employee engagement has significant influence of employees’ productivity; workplace recreation has no significant influence of employees’ productivity; and workplace diversity has significant influence the employees’ productivity. PT. Wenang Permai Sentosa Manado should consider about the importance of the effect of employee engagement, workplace recreation, and workplace diversity in the company. And also, company should make more activities to improve the employee’s feel of connect with the company. Keywords: employee engagement, workplace recreation, employee productivity